Help me with number 2 only.
Spammers maintain social distance.
__/\__
Attachments:
![](https://hi-static.z-dn.net/files/d3e/68a3486506c79ecdaf68c2414a5ed356.jpg)
Answers
Answered by
1
Answer:
Yes
Step-by-step explanation:
x²-2x = (-2)(3-x)
x²-2x = 2x-6
i.e. x²-2x-2x+6 = 0 or x²-4x+6 = 0
which is a quadratic equation.
though am also class X
Answered by
8
Answer:
you right.ಥ‿ಥ ....and thanks for calling me bish... purple you, red you..
Attachments:
![](https://hi-static.z-dn.net/files/d35/0a131b147640157e7549682f32fcefd2.jpg)
Similar questions